Orbital dynamics in the vicinity of asteroid 4660 Nereus - Lang, Anqi; Liu, Xin; Liu, Hu; Jiang, Yu; Liu, Yongjie; Jiang, Chunsheng; Wang, Hua (Advances in space research, 2024)
•The equilibrium points of asteroid 4660 Nereus and their stability are analyzed.•Potentially long-lifetime orbit families in Nereus neighborhood are identified.•Inclined heliotropic orbits and terminator orbits are found to be more stable.•The impact of the SRP, asteroid gravity and polar direction is investigated. Spacecrafts operating in close proximity to small celestial bodies within our Solar System, such as asteroids, face dynamic environments that differ significantly from those encountered in the near-Earth space. Understanding the characteristics of orbital dynamics in the vicinity of asteroids is essential for the successful execution of asteroid exploration missions. Focusing on the asteroid 4660 Nereus, this paper studies the equilibrium points of it and the potentially natural, long-lifetime orbits subject to perturbations from both the asteroid's non-spherical gravitational field and the solar radiation pressure (SRP). Using the semi-analytical method based on averaged Lagrange planetary equations (LPEs), heliotropic and terminator orbits are found more likely to have long lifetimes. It is noteworthy that the conventional near-equatorial heliotropic orbits around Nereus struggle to maintain a long lifetime. In contrast, orbits characterized by a specific inclination and geometry where the apocenter approximately points toward the Sun tend to offer prolonged lifetimes. Moreover, the impact of variations in SRP, gravitational parameter, and pole direction on feasibility of long-term orbit solutions has been explored, resulting in an enhanced comprehension of the intricate orbital dynamics. This study contributes valuable insights for the design of exploration orbits in the vicinity of the Nereus asteroid.